Hybrid Menezes Vanstone-ElGamal ECC Algorithm - Alabiech, Mohammed Hassan; Al-Mashhadi, Haider M. (Iraqi Journal of Science, 2025)
The larger public key techniques in RSA that are currently applied utilize 1024 bits for parameters. The NIST recommends that systems with 1024 bits are suitable for employment until 2010. Then, NIST advises that systems be updated to render security at a high level. One solution is to exploit the previous years of research and analysis in public key and move from former algorithms for public key to the Elliptic Curve (EC). This study suggests a public key technique that is faster than ElGamal ECC. The method in this paper is constructed by two standard methods: the Menezes-Vanstone ECC (MVECC) and the ElGamal ECC. The method is a hybrid of symmetric and asymmetric techniques to generate an asymmetric method. The proposed method does not rely on the Discrete Logarithm Problem (DLP) because the points generated are out of curve. The strategy of the proposed method is much like the ElGamal method, because each symbol generates two points without DLP. In addition, it is like the MVECC because there are no mapping points; in other words, the plaintext is not embedded into EC. It is faster than ElGamal ECC by around 5%–10%.